2009
DOI: 10.3133/ofr20091142
|View full text |Cite
|
Sign up to set email alerts
|

Results of laboratory testing for diphacinone in seawater, fish, invertebrates, and soil following aerial application of rodenticide on Lehua Island, Kauai County, Hawaii, January 2009

Abstract: Island. The limits of detection for diphacinone were 0.4 nanograms per milliliter (parts per billion) seawater, 15 nanograms per gram (dry weight) soil, 20 nanograms per gram (parts per billion) fish fillet, 13 nanograms per gram whole crab, and 34 nanograms per gram soft tissue limpet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(1 reference statement)
1
4
0
Order By: Relevance
“…Toxicant residue from brodifacoum and diphacinone bait products does not appear to be readily incorporated or retained in either of Palmyra's two primary soil types. The results of this current study are in agreement with other findings (Morgan and Wright 1996, Ogilvie et al 1997, Orazio et al 2009) that suggest rodenticides used in broadcast eradications do not transfer high concentrations of toxicants to soil, even in warm, moist conditions where the degradation of bait matrices is rapid. The active ingredients in rodenticides are known for the potential to persist in the environment (Primus et al 2005, Sage et al 2007, Fisher et al 2011), but the low concentration used in bait pellets limits their potential for significant environmental contamination.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Toxicant residue from brodifacoum and diphacinone bait products does not appear to be readily incorporated or retained in either of Palmyra's two primary soil types. The results of this current study are in agreement with other findings (Morgan and Wright 1996, Ogilvie et al 1997, Orazio et al 2009) that suggest rodenticides used in broadcast eradications do not transfer high concentrations of toxicants to soil, even in warm, moist conditions where the degradation of bait matrices is rapid. The active ingredients in rodenticides are known for the potential to persist in the environment (Primus et al 2005, Sage et al 2007, Fisher et al 2011), but the low concentration used in bait pellets limits their potential for significant environmental contamination.…”
Section: Discussionsupporting
confidence: 93%
“…Toxicants deployed during campaigns to control or eradicate invasive rodents may persist in the environment, creating potential exposure pathways for non-target organisms. Anticoagulants are the most widely used rodenticides worldwide (Eason et al 2002, Hoare andHare 2006); however, the migration of toxicants from the bait matrix into soil, and the persistence of toxicant in soil mediums, has rarely been studied in laboratory (Newby and White 1978, Jackson et al 1991, Hall and Priestly 1992, Jackson and Ashton 1992, or in natural settings (Ogilvie et al 1997, Orazio et al 2009, Fisher et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Island within one week of bait application (Orazio et al 2009). Monitoring after a bait trial in 7 2010 on Palmyra Atoll found less than two ppm of diphacinone in the soil after 28, 36, and 50 8 day samples .…”
mentioning
confidence: 99%
“…Diphacinone was not detected by either laboratory in any of the Mōkapu or Lehua samples that were collected after the aerial broadcast of the diphacinone rodenticide (Orazio et al 2009, Primus 2009. Inter-laboratory analysis of duplicate samples corroborates the finding that diphacinone was not present in the marine environment.…”
Section: Resultsmentioning
confidence: 97%